Brain Gym PACE (Positive, Active, Clear, Energetic) as a Cognitive Intervention to Improve Concentration in Elementary School Children - Berliana, Amelia Zaha; Maghfuroh, Lilis; Aisyah, Harnina Samantha (Interest : Jurnal Ilmu Kesehatan, 2025)
Background: Concentration is an important aspect in a child's learning process. A child's ability to focus on a task or lesson material optimally will greatly influence the understanding and learning outcomes achieved. The purpose of this study was to analyze the effect of Brain Gym  PACE on the concentration of children in grades V-VI. Methods: The research design was used a pre-experimental method using one group pre-test and post-test design. The population of this study were students of grades V-VI of SD Muhammadiyah 1 Babat with inclusion and exclusion criteria. The sample was selected using stratified random sampling with a sample size of 76 children. The instruments used were the Army Alpha Intelligence Test questionnaire and SOP Brain Gym  PACE. The intervention was given for 10 minutes a day, 3 times for 3 days. Data were analyzed using the Wilcoxon Sign Rank Test. Results: Based on the results of the Wilcoxon statistics, a significance value of p = <0.001 (p < 0.05) was obtained, which means that there is an influence of Brain Gym on learning concentration. Conclusion: These findings suggest that Brain Gym PACE has a positive effect on improving children’s learning concentration. Educators are advised to implement Brain Gym PACE activities as part of their daily learning routine to support children’s focus and optimize the learning process. Further research is recommended to explore the wider application of Brain Gym across educational contexts and age groups.